(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the issue of preparing future primary school teachers to develop students’ logical thinking using native language lessons as an example. It covers the pedagogical and psychological content of the concept of logical thinking, the didactic potential of native language exercises, and the ways to develop students’ professional competencies in higher education from both theoretical and practical perspectives.